On the Essence of Freedom (Existential Analysis: Journal of the Society for Existential Analysis, 2023)
Informed by Nietzsche's notion of amor fati, Heidegger and Buddhism, Rollo May's understanding of 'essential' as distinct from 'existential' freedom is critiqued and found wanting. The essence of freedom is explicated as unconditional openness: love as our innate capacity for all-inclusive, non-dualistic attunement. The essential, innermost freedom of being transcends both outer, existential, and inner, psychological, freedoms of doing.
Keywords: Freedom; amor fati; authenticity; Buddhism; Gelassenheit; ontological difference; Rollo May